Laboratory results of a 3rd generation roof bolter canopy air curtain for respirable coal mine dust control - W. R. Reed (International Journal of Coal Science & Technology, 2019)
Abstract Testing was completed on an earlier roof bolter CAC that used slots to provide a perimeter airflow. NIOSH tested it due to its unique design that differed from canopies that provided uniform airflow. Based upon NIOSH recommendations from the earlier testing, a 3rd generation roof bolter CAC has been developed by J.H. Fletcher & Co. The changes to this CAC involve design modifications to the plenum outlets, using a single row of outlets on the perimeter and a different material for the plenum. This laboratory testing was a continuation of the original perimeter slotted CAC design. Using gravimetric and instantaneous sampling of respirable dust concentrations underneath and outside of the CAC, the laboratory testing was completed using three different blower fans that delivered differing airflows. The maximum plenum airflow velocities ranged from 2.34 to 3.64 m/s (460–716 fpm). Results showed plenum respirable dust concentrations ranging from 34.6% to 49.3% lower than respirable dust concentrations outside the plenum protection zone, thus showing an improvement in protection for the roof bolter operators.